TINDAK PIDANA MEMASUKKAN KETERANGAN PALSU KEDALAM AKTE AUTENTIK - Annisa Sativa (Universitas Medan Area, 2014)
Society in daily activities can not be separated from the objects associated withthe information under oath , currency , stamp , brand and letter . But fromsome of the objects more often associated with money and letters. Communitylinkages with these objects because people believe in the truth of the object ,wherein the object is a valid object , or even legal , it must be protected sothat no misuse by mimicking or even create an object that is similar but doesnot have the applicable provisions for the legislation . Counterfeiting is a crimewhich can be disturbing people because it can harm others and cause distrusteach other. Law prohibits forgery crime, then anyone who violates theprovisions of the criminal sanctions should apply to run.